ON SOME SUBCLASSES OF MULTIVALENT STARLIKE FUNCTIONS (Journal of Humanitarian and Applied Sciences, 2023)
In the present paper, we introduce two new subclasses T_(m.λ.μ,η,δ)^* (p,α,β,σ) and C_(m,λ,μ,η,δ) ( p,α,β,σ) of multivalent starlike functions in the open unit disk defined by using certain fractional calculus operator. We obtain coefficient inequalities and distortion properties for functions belonging to the above subclasses. The radii of convexity and starlikeness for functions belonging to these subclasses are also determined.
Keywords: multivalent (or p-valent) functions; starlike functions; convex functions; fractional derivative operator